Pengaruh Program Akselerasi Pengembangan Perbankan Syariah (PAPBS) Terhadap Kinerja Keuangan Perbankan Syariah di Indonesia - Miftakhul Khasanah (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
This research aims to analyze the influ- ence of acceleration program develop- ment of sharia banking to performance of sharia banking in Indonesian. This re- search is a comparative research, using quantitative method. Research variables used are profit share, asset share, dpk share, financing extended, ROA, ROE, FDR, FR/ NPFs and GWM/ RR. It focuses on two period: 11 months before and 11 months after Acceleration Development of Sharia Banking Program. This research concludes there is a significant difference in the financial performance of Sharia Banking after the implementation of the Accelera- tion Development Program of Sharia Banking in 2007-2008.